The effects of trans fat diet intake on metabolic parameters and DNA methylation profile in male offspring of in-utero BBA exposed rats / Hala F. S. Abulehia - Abd Karim, Siti Fatma (2023)
Bisphenol A (BPA) is a plasticizer used in the manufacturing of many products, and its involvement in metabolic syndrome risk and development is still not fully understood. Exposure to BPA during critical windows such as pregnancy is known to affect the programming of metabolically active tissues in offspring and increase susceptibility to adverse effects of excessive trans fat diet (TFD) intake. In this study, we aimed to investigate the effect of prenatal BPA exposure with postnatal TFD intake on metabolic and biochemical parameters, pancreatic tissue histology, peroxisome proliferator-activated receptor γ (PPARγ) protein expression, and global DNA methylation expression on adult SD rat offspring. Eighteen pregnant rats were divided into three groups: control (CTL), vehicle tween 80 (VHC), and BPA (5 mg/kg/day) from pregnancy day (PD) 2 to PD 21. Their male rats offspring were then fed either with normal diet (ND) or TFD from postnatal week (PNW) 3 to PNW 14 and were divided into six groups; ND control group (CTLND), TFD control group (CTLTFD), ND vehicle control group (VHCND), TFD vehicle control group (VHCTFD), ND BPA exposed group (BPAND) and TFD BPA exposed group (BPATFD). In offspring, the physiological parameters including body weight, waist circumference, water, and food intake were measured weekly.